The syntactic structures of the shared folktale. - Ben Yahia, Tassadit (El Omda in Linguistics and Discourse Analysis, 2025)
Abstract : Our literary and popular heritage are common. We have always thought of it as Western. The origin is Arab and the branch is Western. It is intertextuality. Since the Ali Baba tales has gained its right of study and analysis, we wanted to include in this article short stories of a realistic type that intersect with the Western Style. Our purpose is to present some tales from the Thousand and One Nights from Western heritage that are derived from the Arabian Nights. The One Thousand- and One-Nights series included different genres between Arabic, Persian and Indian characters, but the main characters are the King Shahryar and his wife Scheherazade, including: the tale of the merchant and the two fraudsters, which we have deliberately analyzed according to the mechanisms of the semiotic method to show the logical control of construction of their narrative form.